The Relationship between Preventive Behavior and Environment with Malaria in Indonesia: Meta-Analysis Study - Ernawati, Kholis; Hilya, F.; Rachmat, D. W. S.; Sholeha, A. A.; Trisiswati, M.; Sari, S. M.; Batubara, L. (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Malaria infection is caused among others by behavioral and environmental factors around the house. Method: The PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analyses) method was used to select articles according to the criteria set by the researcher, and the meta-analysis was a follow-up analysis to determine the difference in the mean of selected articles in the PRISMA protocol. This article analyzes the relationship between preventive behavior factors and the home environment on malaria incidence with a meta-analytic. Study approach—search articles through three electronic journal portal websites with keywords, namely malaria, environment, and Indonesia. The criteria for the article are the time of publication (1 January 2020 to 3 March 2021), preventive behavior, home environment, original research, and case-control study design. Analysis using software Review Manager 5.4. Findings: The results of the literature search using the PRISMA protocol obtained four articles. The results of the analysis showed a positive relationship to malaria, namely variables leaving the house at night (p < 0.0001), ventilation of mosquito net houses (p = 0.01), and puddles of water in the environment around the house (p = 0.05). The results showed that the latest malaria research in Indonesia related to preventive behavior and home environmental factors is still minimal. The results of the study can be used as input for policymakers in controlling malaria.